Method for deeply purifying total organic carbon in high salt water

Through the combined process technology of "activated carbon adsorption + nano-catalyzed ozone oxidation + targeted adsorption", the total organic carbon in chemical waste salt is deeply purified, solving the problem of removing total organic carbon in the resource utilization of waste salt, and achieving efficient and economical waste salt treatment effect.

CN119707078AActive Publication Date: 2025-03-28UNIV OF CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510005481.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-08
Filing Date
2025-01-03
Publication Date
2025-03-28
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The problem of removing total organic carbon in chemical dirty salts affects the effect and efficiency of resource utilization of polluted salts.

Method used

The combined process technology of "activated carbon adsorption + nano-catalyzed ozone oxidation + targeted adsorption" is used to deeply purify the total organic carbon in high brine.

Benefits of technology

The deep purification of high brine total organic carbon is achieved, the cost of waste salt treatment is reduced, and the efficiency and effect of waste salt resource utilization is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707078A_ABST
    Figure CN119707078A_ABST
Patent Text Reader

Abstract

The invention provides a method for deeply purifying total organic carbon in high-salt water, and belongs to the technical field of fine chemical waste salt recycling. Comprising the following steps: S1, removing suspended solids and part of adsorbable total organic carbon in the heavy salt water by adopting an activated carbon adsorption system; s2, oxidizing organic matters in the heavy salt water through a nano ozone catalysis system; s3, the heavy salt water oxidized by the nano ozone catalysis system enters a targeted adsorption system to separate residual total organic carbon in the heavy salt water, and deep purification of the total organic carbon in the heavy salt water is achieved. The method solves the problem of total organic carbon treatment in the current fine chemical waste salt recycling process, reduces the influence of total organic carbon on the waste salt recycling process, and provides engineering application guidance for waste salt recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource utilization of contaminated salt in fine chemical industry, and in particular to a method for deep purification of total organic carbon in high-salt water. Background Art

[0002] my country's chemical industry produces a huge amount of waste salt. It is estimated that the annual discharge of high-salt wastewater exceeds 3×10 8 m 3 The industrial salt produced after treatment is close to 2×10 7 t. Most of the chemical waste salts are soluble inorganic salts, with a small amount of toxic, difficult to degrade organic matter and heavy metals and other impurities, which have been listed as hazardous wastes in the "National List of Hazardous Wastes". In recent years, the treatment and resource utilization of waste salt in chemical production has received increasing attention. The state has also issued relevant documents to encourage and support the resource utilization of waste salt. The market demand for the resource utilization of industrial waste salt is increasing. Efficient and resource-based treatment has become an important issue that the chemical industry urgently needs to overcome. At present, the conventional treatment and disposal process of waste salt is not only difficult, investment and operating costs are high, but also the landfill treatment pressure after stable compliance is very high, especially in fine chemical parks. The problem of waste salt is more prominent. With the rapid development of the fine chemical industry, the exponential growth of salt-containing hazardous solid waste is the biggest bottleneck for the next development of enterprises.

[0003] By recycling industrial waste salt and using it in chemical production to manufacture high-value industrial products such as soda ash and caustic soda, we can eliminate the waste salt problem and reduce the cost of factory landfill of waste salt. At the same time, we can also use waste salt resources to produce new products, extend the product chain, and have good social and economic benefits.

[0004] The main factor restricting the large-scale development of waste salt resource utilization is the removal of organic matter in waste salt. For example, excessive organic pollutant content in brine feed will have an adverse effect on the performance of electrodialysis, ion membrane and electrolyzer. Waste salt, especially waste salt from the chemical industry, has complex composition and many types of organic pollutants. After treatment, the residual impurities, especially the composition of total organic carbon, are uncertain, making it difficult to fully apply existing resource technology processes. Summary of the invention

[0005] The purpose of the present invention is to propose a method for deep purification of total organic carbon in high-salt water. The process of the present invention adopts a combined process technology of "activated carbon adsorption + nano-catalytic ozone oxidation + targeted adsorption" to deeply purify the total organic carbon in high-salt water, truly realizing the resource utilization of contaminated salt.

[0006] The technical solution of the present invention is achieved in this way: The present invention provides a method for deep purification of total organic carbon in high-salt water, comprising the following steps: S1. Use activated carbon adsorption system to remove suspended solids and part of the total organic carbon that can be adsorbed in high salt water; S2. Oxidation of organic matter in high salt water by nano-ozone catalytic system; S3. The high-salt water after oxidation by the nano-ozone catalytic system enters the targeted adsorption system to separate the total organic carbon remaining in the high-salt water, thereby achieving deep purification of the total organic carbon in the high-salt water.

[0007] Activated carbon adsorption is mainly physical adsorption. The adsorption of aromatic hydrocarbon organic matter in salt water can reduce the amount of ozone added in the subsequent ozone catalysis, thereby reducing the treatment cost (the difficulty and cost of degrading aromatic hydrocarbon organic matter with ozone are relatively high). After adsorption, some long-chain, heterocyclic organic matter in the high-salt water will be oxidized into short-chain, alkane compounds and carbon dioxide after ozone catalytic oxidation; finally, the short-chain alkane compounds in the high-salt water are adsorbed through targeted adsorption to achieve the purpose of total organic carbon purification. Through the combined invention of the above processes, deep purification of saturated salt water can be achieved.

[0008] As a further improvement of the present invention, in the active adsorption system, the mass fraction of salt in the high brine is 10% to 26.5%, the adsorption temperature is 40 to 70°C, the pH is 9 to 12, the hydraulic retention time of the activated carbon in contact with the high brine is 30 to 180 minutes, the filling height of the activated carbon bed is 1.0 to 3.0 meters, and when the pressure before and after the adsorption to the bed exceeds 0.06Mpa, backwashing begins, and the strength of the backwash water is 5 to 10L / (s·m 2 ), the intensity of backwash gas is 10~15L / (s·m 2 ).

[0009] As a further improvement of the present invention, the activated carbon is coconut shell activated carbon, and the iodine value ranges from 900 to 1200 mg / g; the activated carbon backwashing cycle is 1 to 3 days, and the backwashing time is 5 to 15 minutes.

[0010] As a further improvement of the present invention, the nano ozone catalytic system includes a nano ozone pre-oxidation system and a nano catalytic ozone oxidation system.

[0011] Nano-scale ozone has a higher solubility in water, which will promote the catalytic oxidation effect. In addition, after ozone is made into nano-scale ozone, the area of ​​contact with pollutants in water is larger, and the reaction efficiency is higher. At the same time, nano-scale ozone will also promote the production of hydroxyl free radicals.

[0012] The core mechanism of ozone catalysis is that dissolved ozone produces hydroxyl radicals under the action of catalyst to oxidize pollutants in wastewater.

[0013] As a further improvement of the present invention, in the nano-ozone pre-oxidation system, air generates oxygen through an oxygen generator, and the generated oxygen enters an ozone generator to generate ozone. The ozone pressure generated by the ozone generator is 0.07-0.09 MPa, and the ozone bubbles are multi-stage cut in the nano-ozone system. The particle size range of the nano-ozone bubbles is 50-200 nm, and the nano-ozone is dissolved in high salt water to pre-oxidize its total organic carbon. The reaction time is 30-120 min, the reaction temperature is 40-60° C., and the reaction pH is 6-9.

[0014] As a further improvement of the present invention, in the nano-catalytic ozone oxidation system, the gas-water mixture is pumped into the catalytic ozone tower through a jet pump, the speed of the jet outlet is 10-15 m / s, the filling height of the fixed bed catalyst is 1.5-4.5 m, the particle size range of the catalyst is 3-5 mm, the contact reaction time of ozone and the catalyst is 30-60 min, the reaction temperature is 40-50° C., the reaction pH is 7-8, the volume ratio of ozone and high salt water is 3 / 1-1 / 1, the total ozone dosage and the total organic carbon mass ratio is about 5 / 1-10 / 1, a pressure regulating valve is arranged on the top of the catalytic ozone tower, the pressure setting range is 0.09-0.12 MPa, the tail gas part is returned to the nano-ozone system to continue the reaction, and the rest is collected to the tail gas destroyer for treatment and then emptied, and the reflux ratio is 2 / 1-5 / 1.

[0015] As a further improvement of the present invention, the catalytic ozone tower adopts a fixed bed form, the catalyst is a heterogeneous catalyst, the heterogeneous catalyst is alumina-based, and the main component loaded is at least one of Mn, Cu, Ni and FeOOH.

[0016] The preparation method of the catalyst is as follows: T1. Preparation of mesoporous alumina: dissolve the porogen in ethanol, adjust the pH value of the solution, add aluminum isopropoxide, stir and mix evenly, heat and stir to react, calcine, and ball mill to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: Glucose and urea are dissolved in water, mesoporous alumina is immersed in the solution, the solvent is evaporated, and calcined to obtain doped N / C mesoporous alumina; T3. MnO2 loading: dissolve manganese salt in water, add doped N / C mesoporous alumina and stir to mix evenly, then add potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat and stir to react, cool to room temperature, filter the product, wash and dry to obtain MnO2 loaded doped N / C mesoporous alumina; T4. Cu / Ni element doping: dissolving copper salt and nickel salt in water, adding MnO2 to load doped N / C mesoporous alumina, impregnating, filtering, washing, drying, calcining, and obtaining a catalyst precursor; T5. Loading of FeOOH: Add the catalyst precursor into water, add ferrous salt and ammonium bicarbonate, heat and stir to react, filter, wash, dry and calcine to obtain the catalyst.

[0017] Preferably, in step T1, the mass ratio of the porogen to aluminum isopropoxide is 1-2:15-20, the pH value of the adjusted solution is 5-6, the temperature of the heated stirring reaction is 70-80°C, the time is 24-36h, the calcination temperature is 400-600°C, the time is 1-3h, and the ball milling time is 1-2h.

[0018] Preferably, in step T2, the mass ratio of glucose, urea and mesoporous alumina is 2-4:1-2:12-15, the calcination temperature is 550-650° C., and the calcination time is 90-150 min.

[0019] Preferably, in step T3, the mass ratio of the manganese salt, doped N / C mesoporous alumina and potassium permanganate is 2-4:10:2.5-3, and the temperature of the heating and stirring reaction is 150-170° C. and the time is 10-14 h.

[0020] Preferably, in step T4, the mass ratio of the copper salt, nickel salt, and MnO2-loaded doped N / C mesoporous alumina is 1-2:0.8-1.2:20-30, and the calcination temperature is 500-600°C and the time is 1-2h.

[0021] Preferably, in step T5, the mass ratio of the catalyst precursor, ferrous salt and ammonium bicarbonate is 10:2-3:7-10, the temperature of the heating and stirring reaction is 60-70°C, the time is 1-3h, and the temperature of the calcination is 300-400°C, and the time is 60-90min.

[0022] Preferably, the porogen is selected from at least one of oxyethylene-oxypropylene triblock copolymers PEO20-PPO70-PEO20 (P123) and PEO106-PPO70-PEO106 (F127).

[0023] Preferably, the manganese salt is selected from at least one of manganese chloride, manganese sulfate and manganese nitrate.

[0024] Preferably, the copper salt is selected from at least one of copper chloride, copper sulfate and copper nitrate.

[0025] Preferably, the nickel salt is selected from at least one of nickel chloride, nickel sulfate and nickel nitrate.

[0026] Preferably, the ferrous salt is ferrous chloride or ferrous sulfate.

[0027] As a further improvement of the present invention, the targeted adsorption system selects targeted adsorbents for adsorption according to the molecular structure and corresponding functional groups of organic pollutants. The filling height of the adsorbent is 1.0-5.0 m, the hydraulic retention time of the adsorbent and the high salt water is 30-90 min, the adsorption temperature is 30-40° C., the adsorption pH is 4-6, and the analytical agent is 2-8% sodium hydroxide solution, and the analytical dosage is 2-4 times the volume of the adsorbent; the rising flow rate of the high salt water is 1.0-5.0 m / h, and the analytical agent flow rate is 1.0-5.0 m / h.

[0028] Targeted adsorption is to selectively adsorb alkane organic matter by changing the structure of the resin surface. Therefore, here, different resins are selected for targeted adsorbents according to the molecular structure and corresponding functional groups of organic pollutants. The adsorbent uses ultra-high correlation polystyrene as the substrate, introduces targeting groups such as acrylamide, cyano, and ester groups, and conducts targeted adsorption of organic pollutants in high salt water according to the structure and polarity of the groups. When organic pollutants contain strong polar functional groups such as carboxylic acids and phenols, adsorbents containing functional groups such as acrylamide and cyano are selected for targeted adsorption; when organic pollutants contain medium polar functional groups such as nitro, dimethylamine, and ethers, adsorbents containing ester groups are selected for targeted adsorption; otherwise, adsorbents without functional groups are selected for adsorption.

[0029] As a further improvement of the present invention, the adsorbent uses ultra-high correlation polystyrene as a substrate, introduces at least one targeting group among acrylamide, cyano and ester groups, and the diameter range of the adsorbent is 0.2 to 2.0 mm.

[0030] As a further improvement of the present invention, the activated carbon tower, ozone catalytic oxidation tower and targeted adsorption tower all adopt a carbon steel lining structure, the lining material includes PP, PO and PE, and the thickness of the lining is 8 to 16 mm.

[0031] Specifically, a method for deep purification of total organic carbon in high-salt water comprises the following steps: S1. Use activated carbon adsorption system to remove suspended solids and part of the total organic carbon that can be adsorbed in high-salt water. The activated carbon adsorption system adopts a fixed bed tower structure. The activated carbon uses coconut shell activated carbon. The iodine value ranges from 900 to 1200 mg / g. The activated carbon bed filling height is 1.0 to 3.0 meters. The hydraulic retention time of the activated carbon in contact with the high-salt water is 30 to 180 minutes. During the contact process, the aromatic hydrocarbon organic matter is adsorbed. The adsorption temperature is 40 to 70 ° C, the pH is 9 to 12, and the suspended solids (ss) in the high-salt water are intercepted at the same time. When the pressure before and after the adsorption to the bed exceeds 0.06Mpa, backwashing begins, and the intensity of the backwash water is 5 to 10L / (s·m 2 ), the intensity of backwash gas is 10~15L / (s·m2 ), the high brine after adsorption enters the next nano-ozone catalytic oxidation unit for further treatment.

[0032] S2. Further oxidize organic matter in high salt water through nano ozone catalytic system. The nano catalytic ozone oxidation system includes two parts: nano ozone pre-oxidation and catalytic ozone oxidation: First, air passes through an oxygen generator to generate oxygen, and the generated oxygen enters an ozone generator to generate ozone. Ozone is cut into nano ozone bubbles with a particle size range of 50 to 200 nm in the nano ozone system in multiple stages, and dissolved in high salt water to pre-oxidize its total organic carbon. The volume ratio of ozone to high salt water is 3 / 1 to 1 / 1, the reaction time is 30 to 120 minutes, the reaction temperature is 40 to 60°C, and the reaction pH is 6 to 9. The gas-water mixture after pre-oxidation is injected into the catalytic ozone oxidation tower through an ejector, the velocity of the jet outlet is 10-15 m / s, the catalytic ozone oxidation tower adopts a fixed bed form, the catalyst adopts a heterogeneous catalyst, the catalyst catalyzes ozone to produce hydroxyl radicals (·OH) to oxidize the total organic carbon in the high salt water that is not adsorbed by the activated carbon, the filling height of the fixed bed catalyst is 1.5-4.5 m, the particle size range of the catalyst is 3-5 mm, the contact reaction time of ozone and the catalyst is 30-60 min, the reaction temperature is 40-50 ° C, the reaction pH is 7-8, the tail gas after the reaction is partially returned to the nano ozone system to continue the reaction, and the rest is collected to the tail gas destroyer for treatment and then emptied, the reflux ratio is 2 / 1-5 / 1, and the oxidized high salt water enters the targeted adsorption system.

[0033] S3. According to the molecular structure and corresponding functional groups of organic pollutants, targeted adsorbents are selected for adsorption. A tower structure is used, the filling height of the adsorbent is 1.0-5.0m, the diameter range of the adsorbent is 0.2-1.5mm, the rising velocity of the high salt water in the adsorption tower is 1.0-5.0m / h, the hydraulic retention time is 30-90min, the adsorption temperature is 30-40℃, and the adsorption pH is 4-6. After adsorption saturation, an analytical agent is used for analysis and activation to ensure the adsorption effect of the targeted adsorbent. The analytical agent uses 2-8% sodium hydroxide solution, the analytical dosage is 2-4 times the volume of the adsorbent, and the analytical agent flow rate is 1.0-5.0m / h. Through targeted adsorption to separate the total organic carbon in the high salt water, the index requirements for entering the salt recovery system are achieved, thereby achieving the purpose of resource utilization of polluted salt.

[0034] The present invention has the following beneficial effects: The main purpose of the present invention is to provide an economical, efficient and stable method for deep purification of total organic carbon, to solve the problem of total organic carbon treatment in the current fine chemical waste salt resource utilization process, to reduce the impact of total organic carbon on the waste salt resource utilization process, and to provide engineering application guidance for waste salt resource utilization.

[0035] The process of the present invention adopts the combined process technology of "activated carbon adsorption + nano-catalytic ozone oxidation + targeted adsorption" to deeply purify the total organic carbon in the high-salt water, truly realizing the resource utilization of polluted salt. Firstly, an activated carbon adsorption system is used to remove suspended solids and part of the total organic carbon that can be adsorbed in the high-salt water. Then, oxygen is generated by an oxygen generator, and the generated oxygen is used to generate ozone through an ozone generator, which is then pumped into a nano-ozone generator through a booster pump to fully mix and react with the high-salt water. In the nano-ozone catalytic system, ozone cut into nano-particles is dissolved in water and pre-oxidized with organic pollutants in the high-salt water. The gas-water mixture after the reaction is injected into a catalytic ozone oxidation tower through an ejector. The catalytic ozone oxidation tower adopts a fixed bed form, and the catalyst adopts a heterogeneous catalyst. The catalyst catalyzes ozone to produce hydroxyl radicals (·OH) to continue to degrade the total organic carbon in the high-salt water. The oxidized high-salt water enters the targeted adsorption system to further separate the total organic carbon that cannot be oxidized and degraded in the brine, so as to achieve the purpose of deep purification of the total organic carbon in the high-salt water. The total organic carbon in the treated high-salt water is less than 10 mg / L. The treated high-salt water enters the salt recovery system to recover the salt therein, thereby achieving the purpose of resource utilization of polluted salt. The present invention fully combines the characteristics of organic pollutants in the sewage brine, and the combined process has a good degradation effect of total organic carbon, has the characteristics of economy, high efficiency and stability, and has a guiding role in engineering applications.

[0036] The present invention prepares a catalytic oxidation catalyst, using mesoporous alumina as a carrier, forming a carrier with a large specific surface area through a porogen, and greatly improving the loading amount of the catalytic metal. Then, by impregnating a solution containing urea and glucose and calcining, the carrier is doped with C / N, and non-metallic elements (such as carbon and nitrogen) are introduced into the carrier to form non-metallic active sites, thereby improving the binding ability of the carrier with the loaded metal oxide and enhancing the affinity of the carrier for ozone molecules, which is conducive to quickly converting ozone molecules into active free radicals, and further improving the degradation ability of the catalyst for organic pollutants.

[0037] Then, the obtained doped N / C mesoporous alumina is loaded with MnO2 through oxidation reaction. Compared with precious metal-loaded catalysts, transition metal oxides such as MnO2 catalysts have the characteristics of wide raw material sources, low price and good anti-toxicity. Then, Cu / Ni is loaded through impregnation and calcination, and the catalytic performance of the catalyst is greatly improved under the synergistic effect. Finally, iron oxyhydroxide (FeOOH) is formed in situ, which further improves the catalytic performance.

[0038] The various metal elements loaded in the catalyst prepared by the present invention have good synergistic catalytic effect. At the same time, with the help of non-metallic elements, it has strong catalytic oxidation effect. The catalyst has large specific surface area, high loading amount, good catalytic performance, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0040] Figure 1 The present invention is a process flow chart of the method for deep purification of total organic carbon in high-salt water. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Preparation Example 1 Preparation of Catalyst Here’s how: T1. Preparation of mesoporous alumina: 1 g of ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 5, 15 g of aluminum isopropoxide was added, stirred and mixed for 15 min, heated to 70 ° C, stirred and reacted for 24 h, calcined at 400 ° C for 1 h, and ball milled for 1 h to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: 2 g of glucose and 1 g of urea were dissolved in 200 mL of water, 12 g of mesoporous alumina was immersed in the solution, the solvent was evaporated, and calcined at 550 ° C for 90 min to obtain doped N / C mesoporous alumina; T3. MnO2 loading: Dissolve 2g of manganese chloride in 200mL of water, add 10g of doped N / C mesoporous alumina and stir to mix evenly, then add 2.5g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 150°C, stir to react for 10h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded doped N / C mesoporous alumina; T4. Cu / Ni doping: 1 g copper chloride and 0.8 g nickel chloride were dissolved in 200 mL water, 20 g MnO2 loaded and doped N / C mesoporous alumina was added, impregnated for 1 h, filtered, washed, dried, and calcined at 500 °C for 1 h to obtain a catalyst precursor; T5. Loading of FeOOH: Add 10 g of catalyst precursor into 200 mL of water, add 2 g of ferrous chloride and 7 g of ammonium bicarbonate, heat to 60°C, stir to react for 1 hour, filter, wash, dry, and calcine at 300°C for 60 minutes to obtain a catalyst.

[0043] Preparation Example 2 Preparation of Catalyst Here’s how: T1. Preparation of mesoporous alumina: 2 g of PEO106-PPO70-PEO106 (F127) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 6, 20 g of aluminum isopropoxide was added, the mixture was stirred for 15 min, heated to 80 ° C, stirred for 36 h, calcined at 600 ° C for 3 h, and ball milled for 2 h to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: 4 g of glucose and 2 g of urea were dissolved in 200 mL of water, 15 g of mesoporous alumina was immersed in the solution, the solvent was evaporated, and calcined at 650 ° C for 150 min to obtain doped N / C mesoporous alumina; T3. MnO2 loading: Dissolve 4g of manganese sulfate in 200mL of water, add 10g of doped N / C mesoporous alumina and stir to mix evenly, then add 3g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 170°C, stir to react for 14h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded doped N / C mesoporous alumina; T4. Cu / Ni doping: 2 g copper sulfate and 1.2 g nickel sulfate were dissolved in 200 mL water, 30 g MnO2 loaded and doped N / C mesoporous alumina was added, impregnated for 1 h, filtered, washed, dried, and calcined at 600 °C for 2 h to obtain a catalyst precursor; T5. Loading of FeOOH: Add 10 g of catalyst precursor into 200 mL of water, add 3 g of ferrous sulfate and 10 g of ammonium bicarbonate, heat to 70°C, stir and react for 3 h, filter, wash, dry, and calcine at 400°C for 90 min to obtain a catalyst.

[0044] Preparation Example 3 Preparation of Catalyst Here’s how: T1. Preparation of mesoporous alumina: 1.5 g of ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 5.5, 17 g of aluminum isopropoxide was added, stirred and mixed for 15 min, heated to 75 ° C, stirred and reacted for 30 h, calcined at 500 ° C for 2 h, and ball milled for 1.5 h to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: 3 g of glucose and 1.5 g of urea were dissolved in 200 mL of water, 13.5 g of mesoporous alumina was immersed in the solution, the solvent was evaporated, and calcined at 600 ° C for 120 min to obtain doped N / C mesoporous alumina; T3. MnO2 loading: Dissolve 3g of manganese sulfate in 200mL of water, add 10g of doped N / C mesoporous alumina and stir to mix evenly, then add 2.7g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 160°C, stir to react for 12h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded doped N / C mesoporous alumina; T4. Cu / Ni doping: 1.5 g copper nitrate and 1 g nickel nitrate were dissolved in 200 mL water, 25 g MnO2 loaded and doped N / C mesoporous alumina was added, impregnated for 1 h, filtered, washed, dried, and calcined at 550 °C for 1.5 h to obtain a catalyst precursor; T5. Loading of FeOOH: 10 g of catalyst precursor was added to 200 mL of water, 2.5 g of ferrous chloride and 8 g of ammonium bicarbonate were added, the mixture was heated to 65°C, stirred for reaction for 2 h, filtered, washed, dried, and calcined at 350°C for 75 min to obtain a catalyst.

[0045] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that the ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) is not added in step T1.

[0046] The details are as follows: T1. Preparation of alumina: 200 mL of ethanol was used to adjust the pH value of the solution to 5.5, 17 g of aluminum isopropoxide was added, the mixture was stirred for 15 min, the mixture was heated to 75 ° C, the mixture was stirred for 30 h, the mixture was calcined at 500 ° C for 2 h, and the mixture was ball-milled for 1.5 h to obtain alumina; T2. Preparation of doped N / C alumina: 3 g of glucose and 1.5 g of urea were dissolved in 200 mL of water, 13.5 g of mesoporous alumina was impregnated in the solution, the solvent was evaporated, and calcined at 600 ° C for 120 min to obtain doped N / C alumina; T3. MnO2 loading: Dissolve 3g of manganese sulfate in 200mL of water, add 10g of doped N / C alumina and stir to mix evenly, then add 2.7g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 160°C, stir to react for 12h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded doped N / C alumina; T4. Cu / Ni doping: 1.5 g copper nitrate and 1 g nickel nitrate were dissolved in 200 mL water, 25 g MnO2 loaded and doped N / C alumina was added, impregnated for 1 h, filtered, washed, dried, and calcined at 550 °C for 1.5 h to obtain a catalyst precursor; T5. Loading of FeOOH: 10 g of catalyst precursor was added to 200 mL of water, 2.5 g of ferrous chloride and 8 g of ammonium bicarbonate were added, the mixture was heated to 65°C, stirred for reaction for 2 h, filtered, washed, dried, and calcined at 350°C for 75 min to obtain a catalyst.

[0047] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that step T2 is not performed.

[0048] The details are as follows: T1. Preparation of mesoporous alumina: 1.5 g of ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 5.5, 17 g of aluminum isopropoxide was added, stirred and mixed for 15 min, heated to 75 ° C, stirred and reacted for 30 h, calcined at 500 ° C for 2 h, and ball milled for 1.5 h to obtain mesoporous alumina; T2. MnO2 loading: Dissolve 3g of manganese sulfate in 200mL of water, add 10g of mesoporous alumina and stir to mix evenly, then add 2.7g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 160°C, stir to react for 12h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded mesoporous alumina; T3. Cu / Ni doping: 1.5 g copper nitrate and 1 g nickel nitrate were dissolved in 200 mL water, 25 g MnO2-loaded mesoporous alumina was added, and the mixture was immersed for 1 h, filtered, washed, dried, and calcined at 550 °C for 1.5 h to obtain a catalyst precursor; T4. Loading of FeOOH: 10 g of catalyst precursor was added to 200 mL of water, 2.5 g of ferrous chloride and 8 g of ammonium bicarbonate were added, the mixture was heated to 65°C, stirred for reaction for 2 h, filtered, washed, dried, and calcined at 350°C for 75 min to obtain a catalyst.

[0049] Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that step T3 is not performed.

[0050] The details are as follows: T1. Preparation of mesoporous alumina: 1.5 g of ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 5.5, 17 g of aluminum isopropoxide was added, stirred and mixed for 15 min, heated to 75 ° C, stirred and reacted for 30 h, calcined at 500 ° C for 2 h, and ball milled for 1.5 h to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: 3 g of glucose and 1.5 g of urea were dissolved in 200 mL of water, 13.5 g of mesoporous alumina was immersed in the solution, the solvent was evaporated, and calcined at 600 ° C for 120 min to obtain doped N / C mesoporous alumina; T3. Cu / Ni doping: 1.5 g copper nitrate and 1 g nickel nitrate were dissolved in 200 mL water, 25 g doped N / C mesoporous alumina was added, and the mixture was immersed for 1 h, filtered, washed, dried, and calcined at 550° C. for 1.5 h to obtain a catalyst precursor; T4. Loading of FeOOH: 10 g of catalyst precursor was added to 200 mL of water, 2.5 g of ferrous chloride and 8 g of ammonium bicarbonate were added, the mixture was heated to 65°C, stirred for reaction for 2 h, filtered, washed, dried, and calcined at 350°C for 75 min to obtain a catalyst.

[0051] Comparative Preparation Example 4 Compared with Preparation Example 3, the difference is that step T4 is not performed. The details are as follows: T1. Preparation of mesoporous alumina: 1.5 g of ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 5.5, 17 g of aluminum isopropoxide was added, stirred and mixed for 15 min, heated to 75 ° C, stirred and reacted for 30 h, calcined at 500 ° C for 2 h, and ball milled for 1.5 h to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: 3 g of glucose and 1.5 g of urea were dissolved in 200 mL of water, 13.5 g of mesoporous alumina was immersed in the solution, the solvent was evaporated, and calcined at 600 ° C for 120 min to obtain doped N / C mesoporous alumina; T3. MnO2 loading: Dissolve 3g of manganese sulfate in 200mL of water, add 10g of doped N / C mesoporous alumina and stir to mix evenly, then add 2.7g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 160°C, stir to react for 12h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded doped N / C mesoporous alumina; T4. Loading of FeOOH: Add 10g MnO2 loaded doped N / C mesoporous alumina into 200mL water, add 2.5g ferrous chloride and 8g ammonium bicarbonate, heat to 65°C, stir to react for 2h, filter, wash, dry, and calcine at 350°C for 75min to obtain the catalyst.

[0052] Comparative Preparation Example 5 Compared with Preparation Example 3, the difference is that step T5 is not performed.

[0053] The details are as follows: T1. Preparation of mesoporous alumina: 1.5 g of ethylene oxide-propylene oxide triblock copolymer PEO20-PPO70-PEO20 (P123) was dissolved in 200 mL of ethanol, the pH value of the solution was adjusted to 5.5, 17 g of aluminum isopropoxide was added, stirred and mixed for 15 min, heated to 75 ° C, stirred and reacted for 30 h, calcined at 500 ° C for 2 h, and ball milled for 1.5 h to obtain mesoporous alumina; T2. Preparation of doped N / C mesoporous alumina: 3 g of glucose and 1.5 g of urea were dissolved in 200 mL of water, 13.5 g of mesoporous alumina was immersed in the solution, the solvent was evaporated, and calcined at 600 ° C for 120 min to obtain doped N / C mesoporous alumina; T3. MnO2 loading: Dissolve 3g of manganese sulfate in 200mL of water, add 10g of doped N / C mesoporous alumina and stir to mix evenly, then add 2.7g of potassium permanganate, transfer the solution to a stainless steel reactor with a polytetrafluoroethylene liner, seal, heat to 160°C, stir to react for 12h, cool to room temperature, filter, wash and dry the product to obtain MnO2 loaded doped N / C mesoporous alumina; T4. Doping of Cu / Ni elements: Dissolve 1.5 g of copper nitrate and 1 g of nickel nitrate in 200 mL of water, add 25 g of MnO2 loaded and doped N / C mesoporous alumina, soak for 1 h, filter, wash, dry, and calcine at 550 °C for 1.5 h to obtain the catalyst.

[0054] Test Example 1 The catalysts prepared in Preparation Examples 1-3 of the present invention and Comparative Preparation Examples 1-5 were measured for specific surface area and pore volume using an ASAP2460 fully automatic specific surface and porosity analyzer produced by Micromeritics Instruments, Inc., USA. The results are shown in Table 1.

[0055] Table 1

[0056] It can be seen from the above table that the catalysts prepared in Preparation Examples 1-3 of the present invention have a larger specific surface area and a larger pore volume.

[0057] Test Example 2 The catalyst prepared in Preparation Example 1-3 or Comparative Preparation Example 1-5 was added to the catalytic ozone system, the initial dosage was 150 g / L, the ozone inlet mass concentration was set to 9 mg / L, and the reaction time was set to 40 min. The initial simulated wastewater had a tetracycline mass concentration of 100 mg / L and a pH of 7. After continuous treatment for 40 min, 5 mL of simulated wastewater was taken, and the simulated wastewater was filtered through a water filter membrane with a pore size of 0.45 μm, and the absorbance was measured using an ultraviolet spectrophotometer to calculate the mass concentration of tetracycline. The results are shown in Table 2.

[0058] Table 2

[0059] It can be seen from the above table that the catalysts prepared in Preparation Examples 1-3 of the present invention have a good effect of catalyzing ozone oxidation and degradation of organic matter.

[0060] Example 1 Combination Figure 1 Process flow, the method described in this embodiment includes the following steps: S1. For the chemical high-salt wastewater system with a mass fraction of 15%, an activated carbon adsorption system is used to remove suspended solids and part of the total organic carbon that can be adsorbed in the high-salt water. The activated carbon adsorption system adopts a fixed bed tower structure, and the activated carbon uses coconut shell activated carbon. The iodine value range is 1000mg / g, and the activated carbon bed filling height is 1.5 meters. The hydraulic retention time of the activated carbon in contact with the high-salt water is 30min. During the contact process, the aromatic hydrocarbon organic matter is adsorbed. The adsorption temperature is 55℃ and the pH is 10. At the same time, the ss in the high-salt water is intercepted. When the pressure before and after the adsorption to the bed exceeds 0.06Mpa, backwashing begins, and the intensity of the backwash water is 5.0L / (s·m 2 ), the intensity of backwash gas is 10L / (s·m 2 ), backwash for 5 minutes.

[0061] When the bed pressure drops and the high brine is adsorbed, it enters the next nano-ozone catalytic oxidation unit for further treatment.

[0062] S2. Further oxidize organic matter in high salt water through nano ozone catalytic system. The nano catalytic ozone oxidation system includes two parts: nano ozone pre-oxidation and catalytic ozone oxidation: First, air generates oxygen through an oxygen generator, and the generated oxygen enters an ozone generator to generate ozone with an ozone concentration of 120-140 mg / L. Ozone is cut into nano ozone bubbles with a particle size range of 100-200 nm in the nano ozone system in multiple stages, and dissolved in high salt water to pre-oxidize its total organic carbon. The volume ratio of ozone to high salt water is 1 / 1, the reaction time is 30 min, the reaction temperature is 45 ° C, and the reaction pH is 7.5. The gas-water mixture after pre-oxidation is injected into the catalytic ozone oxidation tower through an ejector, and the velocity of the jet outlet is 10m / s. The catalytic ozone oxidation tower adopts a fixed bed form, and the catalyst adopts a heterogeneous catalyst. The catalyst catalyzes ozone to produce hydroxyl radicals (·OH) to oxidize the total organic carbon in the high salt water that is not adsorbed by the activated carbon. The filling height of the fixed bed catalyst is 2.5m, and the particle size range of the catalyst is 3-5mm. The contact reaction time of ozone and the catalyst is 30min, the reaction temperature is 45℃, and the reaction pH is 7.5. Part of the tail gas after the reaction is returned to the nano ozone system to continue the reaction, and the rest is collected in the tail gas destroyer for treatment and then emptied. The reflux ratio is 2 / 1, and the oxidized high salt water enters the targeted adsorption system.

[0063] S3. According to the molecular structure and corresponding functional groups of organic pollutants, adsorbents without functional groups are selected for adsorption. A tower structure is used, the filling height of the adsorbent is 1.5m, the diameter range of the adsorbent is 0.2-1.5mm, the rising velocity of the high salt water in the adsorption tower is 3.0m / h, the hydraulic retention time is 45min, the adsorption temperature is 35℃, and the adsorption pH is 5.5. After adsorption saturation, an analytical agent is used for analysis and activation. The analytical agent uses 8% sodium hydroxide solution, the analytical dosage is 3 times the volume of the adsorbent, and the analytical agent flow rate is 3.0m / h. The total organic carbon in the high salt water is separated by targeted adsorption, and enters the salt recovery system after meeting the requirements.

[0064] Example 2 Combination Figure 1 Process flow, the method described in this embodiment includes the following steps: S1. For the chemical high-salt wastewater system with a mass fraction of 20%, an activated carbon adsorption system is used to remove suspended solids and part of the total organic carbon that can be adsorbed in the high-salt water. The activated carbon adsorption system adopts a fixed bed tower structure, and the activated carbon uses coconut shell activated carbon. The iodine value range is 1000mg / g, and the activated carbon bed filling height is 2.0 meters. The hydraulic retention time of the activated carbon in contact with the high-salt water is 60min. During the contact process, the aromatic hydrocarbon organic matter is adsorbed. The adsorption temperature is 55℃ and the pH is 10. At the same time, the ss in the high-salt water is intercepted. When the pressure before and after the adsorption to the bed exceeds 0.06Mpa, backwashing begins, and the intensity of the backwash water is 7.0L / (s·m 2 ), the intensity of backwash gas is 12L / (s·m 2 ), backwash for 10 minutes.

[0065] When the bed pressure drops and the high brine is adsorbed, it enters the next nano-ozone catalytic oxidation unit for further treatment.

[0066] S2. Further oxidize organic matter in high salt water through nano ozone catalytic system. The nano catalytic ozone oxidation system includes two parts: nano ozone pre-oxidation and catalytic ozone oxidation: First, air generates oxygen through an oxygen generator, and the generated oxygen enters an ozone generator to generate ozone with an ozone concentration of 120-140 mg / L. Ozone is cut into nano ozone bubbles with a particle size range of 100-200 nm in the nano ozone system in multiple stages, and dissolved in high salt water to pre-oxidize its total organic carbon. The volume ratio of ozone to high salt water is 2 / 1, the reaction time is 45 min, the reaction temperature is 45 ° C, and the reaction pH is 7.5. The gas-water mixture after pre-oxidation is injected into the catalytic ozone oxidation tower through an ejector, and the velocity of the jet outlet is 15m / s. The catalytic ozone oxidation tower adopts a fixed bed form, and the catalyst adopts a heterogeneous catalyst. The catalyst catalyzes ozone to produce hydroxyl radicals (·OH) to oxidize the total organic carbon in the high salt water that is not adsorbed by the activated carbon. The filling height of the fixed bed catalyst is 3.0m, and the particle size range of the catalyst is 3-5mm. The contact reaction time of ozone and the catalyst is 45min, the reaction temperature is 45℃, and the reaction pH is 7.5. Part of the tail gas after the reaction is returned to the nano ozone system to continue the reaction, and the rest is collected in the tail gas destroyer for treatment and then emptied. The reflux ratio is 3 / 1, and the oxidized high salt water enters the targeted adsorption system.

[0067] S3. According to the molecular structure and corresponding functional groups of organic pollutants, ester-containing adsorbents are selected for targeted adsorption. A tower structure is used, the filling height of the adsorbent is 2.0m, the diameter range of the adsorbent is 0.2-1.5mm, the rising velocity of the high-salt water in the adsorption tower is 2.0m / h, the hydraulic retention time is 60min, the adsorption temperature is 35℃, and the adsorption pH is 4.0. After adsorption saturation, an analytical agent is used for analysis and activation. The analytical agent uses a 6% sodium hydroxide solution, the analytical dosage is 2.5 times the volume of the adsorbent, and the analytical agent flow rate is 2.0m / h. The total organic carbon in the high-salt water is separated by targeted adsorption, and enters the salt recovery system after meeting the requirements.

[0068] Example 3 Combination Figure 1 Process flow, the method described in this embodiment includes the following steps: S1. For the chemical high-salt wastewater system with a mass fraction of 25%, an activated carbon adsorption system is used to remove suspended solids and part of the total organic carbon that can be adsorbed in the high-salt water. The activated carbon adsorption system adopts a fixed bed tower structure, and the activated carbon uses coconut shell activated carbon. The iodine value range is 1100mg / g, and the activated carbon bed filling height is 2.5 meters. The hydraulic retention time of the activated carbon in contact with the high-salt water is 60min. During the contact process, the aromatic hydrocarbon organic matter is adsorbed. The adsorption temperature is 55℃ and the pH is 10. At the same time, the ss in the high-salt water is intercepted. When the pressure before and after the adsorption to the bed exceeds 0.06Mpa, backwashing begins, and the intensity of the backwash water is 10.0L / (s·m 2 ), the intensity of backwash gas is 15L / (s·m 2 ), backwash for 15 minutes.

[0069] When the bed pressure drops and the high brine is adsorbed, it enters the next nano-ozone catalytic oxidation unit for further treatment.

[0070] S2. Further oxidize organic matter in high salt water through nano ozone catalytic system. The nano catalytic ozone oxidation system includes two parts: nano ozone pre-oxidation and catalytic ozone oxidation: First, air generates oxygen through an oxygen generator, and the generated oxygen enters an ozone generator to generate ozone with an ozone concentration of 120-140 mg / L. Ozone is cut into nano ozone bubbles with a particle size range of 50-100 nm in the nano ozone system in multiple stages, and dissolved in high salt water to pre-oxidize its total organic carbon. The volume ratio of ozone to high salt water is 3 / 1, the reaction time is 60 min, the reaction temperature is 45 ° C, and the reaction pH is 7.5. The gas-water mixture after pre-oxidation is injected into the catalytic ozone oxidation tower through an ejector, and the velocity of the jet outlet is 12m / s. The catalytic ozone oxidation tower adopts a fixed bed form, and the catalyst adopts a heterogeneous catalyst. The catalyst catalyzes ozone to produce hydroxyl radicals (·OH) to oxidize the total organic carbon in the high salt water that is not adsorbed by the activated carbon. The filling height of the fixed bed catalyst is 4.0m, and the particle size range of the catalyst is 3-5mm. The contact reaction time of ozone and the catalyst is 60min, the reaction temperature is 45℃, and the reaction pH is 7.5. Part of the tail gas after the reaction is returned to the nano ozone system to continue the reaction, and the rest is collected in the tail gas destroyer for treatment and then emptied. The reflux ratio is 4 / 1, and the oxidized high salt water enters the targeted adsorption system.

[0071] S3. According to the molecular structure and corresponding functional groups of organic pollutants, an adsorbent containing acrylamide is selected for targeted adsorption. A tower structure is used, the filling height of the adsorbent is 3.5m, the diameter range of the adsorbent is 0.2-1.5mm, the rising velocity of the high salt water in the adsorption tower is 1.0m / h, the hydraulic retention time is 60min, the adsorption temperature is 35℃, and the adsorption pH is 4.0. After adsorption saturation, an analytical agent is used for analysis and activation. The analytical agent uses a 4% sodium hydroxide solution, the analytical dosage is 4.0 times the volume of the adsorbent, and the analytical agent flow rate is 1.0m / h. The total organic carbon in the high salt water is separated by targeted adsorption, and enters the salt recovery system after meeting the requirements.

[0072] After the above treatment, the main treatment effects are summarized in Table 3: Table 3 Summary of treatment effects of the embodiments

[0073] It can be seen from the above table that the combined process of the present invention can achieve a total organic carbon removal rate of 97.6%, which has a very good removal effect.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for deep purification of total organic carbon in high-salt water, characterized in that: The following steps are involved: S1. Use activated carbon adsorption system to remove suspended solids and part of the total organic carbon that can be adsorbed in high salt water; S2. Oxidation of organic matter in high salt water by nano-ozone catalytic system; S3. The high-salt water after oxidation by the nano-ozone catalytic system enters the targeted adsorption system to separate the total organic carbon remaining in the high-salt water, thereby achieving deep purification of the total organic carbon in the high-salt water.

2. The method according to claim 1, characterized in that In the active adsorption system, the mass fraction of salt in the high brine is 10% to 26.5%, the adsorption temperature is 40 to 70°C, the pH is 9 to 12, the hydraulic retention time of the activated carbon in contact with the high brine is 30 to 180 minutes, the filling height of the activated carbon bed is 1.0 to 3.0 meters, and when the pressure before and after the adsorption to the bed exceeds 0.06Mpa, backwashing begins, and the strength of the backwash water is 5 to 10L / (s·m 2 ), the intensity of backwash gas is 10~15L / (s·m 2 ).

3. The method according to claim 2, characterized in that The activated carbon used is coconut shell activated carbon, and the iodine value ranges from 900 to 1200 mg / g; the activated carbon backwashing cycle is 1 to 3 days, and the backwashing time is 5 to 15 minutes.

4. The method according to claim 1, characterized in that The nano ozone catalytic system comprises a nano ozone pre-oxidation system and a nano catalytic ozone oxidation system.

5. The method according to claim 4, characterized in that In the nano-ozone pre-oxidation system, air generates oxygen through an oxygen generator, and the generated oxygen enters an ozone generator to generate ozone. The ozone pressure generated by the ozone generator is 0.07-0.09 MPa. The ozone bubbles are multi-stage cut in the nano-ozone system, and the particle size range of the nano-ozone bubbles is 50-200 nm. The nano-ozone is dissolved in high salt water to pre-oxidize its total organic carbon. The reaction time is 30-120 min, the reaction temperature is 40-60° C., and the reaction pH is 6-9.

6. The method according to claim 4, characterized in that In the nano-catalytic ozone oxidation system, a gas-water mixture is pumped into a catalytic ozone tower through a jet pump, the velocity of the jet outlet is 10-15 m / s, the filling height of the fixed bed catalyst is 1.5-4.5 m, the particle size range of the catalyst is 3-5 mm, the contact reaction time of ozone and the catalyst is 30-60 min, the reaction temperature is 40-50° C., the reaction pH is 7-8, the volume ratio of ozone to high salt water is 3 / 1-1 / 1, the total ozone dosage and the total organic carbon mass ratio is 5 / 1-10 / 1, a pressure regulating valve is arranged on the top of the catalytic ozone tower, the pressure setting range is 0.09-0.12 MPa, the tail gas part is returned to the nano-ozone system to continue the reaction, and the rest is collected to the tail gas destroyer for treatment and then emptied, and the reflux ratio is 2 / 1-5 / 1.

7. The method according to claim 6, characterized in that The catalytic ozone tower adopts a fixed bed form, and the catalyst is a heterogeneous catalyst. The heterogeneous catalyst is alumina-based, and the main component loaded is at least one of Mn, Cu, Ni and FeOOH.

8. The method according to claim 1, characterized in that The targeted adsorption system selects targeted adsorbents for adsorption according to the molecular structure and corresponding functional groups of organic pollutants. The filling height of the adsorbent is 1.0-5.0m, the hydraulic retention time of the adsorbent and the high salt water is 30-90min, the adsorption temperature is 30-40°C, the adsorption pH is 4-6, and the analytical agent uses 2-8% sodium hydroxide solution, and the analytical dosage is 2-4 times the volume of the adsorbent; the rising flow rate of the high salt water is 1.0-5.0m / h, and the analytical agent flow rate is 1.0-5.0m / h.

9. The method according to claim 1, characterized in that: The activated carbon tower, ozone catalytic oxidation tower and targeted adsorption tower used all adopt carbon steel lining structure. The lining materials include PP, PO and PE. The thickness of the lining is 8 to 16 mm.

10. The method according to claim 8, characterized in that The adsorbent uses ultra-high correlation polystyrene as a substrate, introduces at least one targeting group among acrylamide, cyano and ester groups, and the diameter range of the adsorbent is 0.2-2.0 mm.

Citation Information

Patent Citations

  • Cleaner production technology for renewable targeted adsorption and pretreated organic biorefractory wastewater

    CN107253807A

  • Heterogeneous ozone catalysis and micro-nano gas bubble combined sewage treatment method

    CN110540285A

  • Method and device for efficiently catalyzing ozone to deeply treat sewage

    CN112777722A

  • Efficient purification treatment method for printing and dyeing wastewater

    CN116903190A

  • Device for removing organic matters in high-salinity wastewater

    CN214829529U